Investigating the effects of market segmentation on firm survival and their heterogeneities in China. (9th August 2021) - Li, Peixin; Li, Lixia; Xie, Yichun; Zhang, Xueliang
Abstract: The paper uses the hazards model to estimate how market segmentation affects firm survival and accompanied resource allocation efficiency in China based on the manufacturing firm's data in 1998–2007 from the Annual Survey of Industrial Firms, considering the time‐varying and heterogeneous effect with the dynamics and characteristics of enterprises. According to the results, although firms benefit from market segmentation in the inauguration period, the protection diminishes afterwards and eventually becomes a hazard to the firm survival. This paper also takes one step further in finding that market segmentation may distort the resource allocation by protecting low‐productivity and low‐profitability firms from exiting the market. The findings suggest that local governments should strengthen cooperation to break administrative barriers and promote regional integrated development in order to realize the benefits of the domestic super‐large‐scale market.